Teaching and learning of college mathematics and student mathematical thinking : are the lines of the same track? / Parmjit Singh ... [et al.] - Singh, Parmjit; Teoh, Sian Hoon; Rasid, Nor Syazwani; Md Nasir, Nurul Akmal; Cheong, Tau Han; Abdul Rahman, Norziah (Universiti Teknologi MARA, 2016)
Studies related to school mathematics have shown that students who scored well on standardized tests often are unable to successfully use memorized facts and formulae in real-life application outside the classroom. The outcome of TIMSS and PISA studies further emphasizes the importance of mathematics teaching and learning in the Malaysian education system. Various measures have been taken by the Ministry of Education to enhance the teaching and learning of mathematics in schools. However, issues related to college mathematics have yet to be addressed.In the past decade, universities have been bogged down with ranking systems(such as Times Higher Education University Rankings, QS ranking) and Quality Indicators for Learning and Teaching related to issues such as studentsgraduating on time (GOT). In this paper, we investigate the finer points of mathematics teaching and learning. Our premise is that practical knowledge (common sense) and mathematics knowledge are closely related in the learning of mathematics in college.Three case studies are discussed in this paper to highlight this premise. These studies revealed that college students gradually practices rote learning and their final grades do not reflect the development of mathematical thinking. Furthermore, the teaching approach that focuses on computation deters students from fully developing their understanding of why or when they should be applied. Teaching instructions should shift from learning the rules for operations to understanding mathematical concepts which promotes the development of mathematical thinking. Students should be equipped with “problem solving tools” that would allow them to be accommodative to changing needs (Treffinger, 2008). It involves the acquisition and application of mathematics concepts and skills in a wide range of situations, including non-routine and real world problems to provide learning opportunities for problem solving. Hence we strongly propose mathematical problem solving as a new course central in the development of mathematical thinking at the tertiary level.